The philosophy of Saint Thomas Aquinas : a sketch - Brock, Stephen Louis (James Clarke & Co., 2016)
If Saint Thomas Aquinas was a great theologian, it is in no small part because he was a great philosopher. And he was a great philosopher because he was a great metaphysician. In the twentieth century, metaphysics was not much in vogue, among either theologians or even philosophers; but now it is making a comeback, and once the contours of Thomas's metaphysical vision are glimpsed, it looks like anything but a museum piece. It only needs some dusting off. Many are studying Thomas now for the answers that he might be able to give to current questions, but he is perhaps even more interesting for the questions that he can raise regarding current answers: about the physical world, about human life and knowledge, and (needless to say) about God. This book is aimed at helping those who are not experts in medieval thought to begin to enter into Thomas's philosophical point of view. Along the way, it brings out some aspects of his thought that are not often emphasized in the current literature, and it offers a reading of his teaching on the divine nature that goes rather against the drift of some prominent recent interpretations.